Since both equations given are equal to y, we can set them equal to each other and solve for x.
−6x = −4x+2
Adding 4x to both sides:
−6x+4x = 2
Simplifying:
−2x = 2
Dividing both sides by -2:
x = -1
Now that we have the value of x, we can substitute it back into one of the equations to solve for y.
y = −6(-1)
y = 6
Therefore, the solution to the system of equations is x = -1 and y = 6.
Solve the system by substitution.
y, equals, minus, 6, x
y=
−6x
y, equals, minus, 4, x, plus, 2
y=
−4x+2
1 answer